2018
DOI: 10.1080/1828051x.2018.1424569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on lipid peroxidation of fresh and frozen-thawed semen of Nili-Ravi buffalo bulls

Abstract: Buffalo bull spermatozoa are rich in polyunsaturated fatty acids and are prone to lipid peroxidation. We hypothesised that lipid peroxidation in buffalo bull semen will increase with age and will affect the semen quality. The objective was to compare malondialdehyde (MDA) concentration and the quality of fresh and frozen-thawed semen between aged (13.6 ± 1.0 years; n ¼ 3) and young (3.4 ± 0.3 years; n ¼ 3) Nili-Ravi bulls. The concentration of MDA did not differ (p >.05) between aged vs. young bulls in fresh (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
2
17
1
Order By: Relevance
“…At 7 years old, swamp buffalo bull had the poorest (P<0.01) sperms motility postthawing and recovery rate compared to 5 and 6 years old. In line with this finding, Ahmed et al (2018) also found that aged buffalo bulls had lower sperms motility post-thawing than the young bulls. In other livestock such as dairy cattle, it was also reported that the bull age had a significant effect on sperms motility post-thawing (Murphy et al, 2018).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…At 7 years old, swamp buffalo bull had the poorest (P<0.01) sperms motility postthawing and recovery rate compared to 5 and 6 years old. In line with this finding, Ahmed et al (2018) also found that aged buffalo bulls had lower sperms motility post-thawing than the young bulls. In other livestock such as dairy cattle, it was also reported that the bull age had a significant effect on sperms motility post-thawing (Murphy et al, 2018).…”
Section: Resultssupporting
confidence: 77%
“…Previously, Amin et al (1999) showed that sperms motility post-thawing of swamp buffalo bulls ranged from 41.43 to 55.71%. In another study, Ahmed et al (2018) found that sperms motility post-thawing of Nili-Ravi buffalo bulls was between 43.80 to 46.60%.…”
Section: Resultsmentioning
confidence: 95%
“…Sperm abnormality can be categorized as primary or secondary abnormality both have different causes. Primary abnormality ccurred on the spermatogenesis process inside testis because the maturation process of sperm did not function properly, while secondary abnormality often occurred after sperm cells leaving tubulous seminiferous or outside main reproductive organs [21]. Sperm abnormality on frozen semen generally classified as a secondary abnormality which was caused by few defections on several parts of the sperm cell body especially on sperm tail.…”
Section: Sperm Abnormalitymentioning
confidence: 99%
“…Malondialdehyde concentration in frozenthawed Nili-Ravi buffalo bull semen was assessed as described by Ahmed et al, (2018). Briefly semen was mixed with 8% (w/v) sodium dodecyl sulfate solution followed by addition of 20% (v/v) acetic acid.…”
Section: Catalase and Lipid Peroxidation Assessmentmentioning
confidence: 99%